Bezpośrednie inwestycje zagraniczne i ich wpływ na wzrost gospodarczy krajów OECD - Stawicka, Magdalena (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The main aim of this article is to show the position and the meaning of foreign direct investment in the OECD countries and their influence on the basic macroeconomic index, which is real GDP in percentage. The article paid special attention to the fact that there is a strong relationship between inflow of foreign direct investment and real GDP in percentage appeear to have. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (16); 2008; nr 1193, s. 335-349